2021
DOI: 10.1093/molbev/msab262
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Phenotypic Evolution of Rhodopsin for Dim-Light Sensing across Deep-Diving Vertebrates

Abstract: Rhodopsin comprises an opsin attached to a retinal chromophore, and is the only visual pigment conferring dim-light vision in vertebrates. On activation by photons, the retinal group becomes detached from the opsin, which is then inactive until it is recharged. Of all vertebrate species, those that dive face unique visual challenges, experiencing rapid decreases in light level and hunting in near darkness. Here we combine sequence analyses with functional assays to show that the rhodopsin pigments of four dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Our results revealed a significant correlation between COL8A2 evolution and maximum diving depth (Figure 8), which indicated selection on genes imposed by diving depth. This conclusion is consistent with the finding of a previous study on RH1 that water depth adaptation has a significant impact on the evolution of vision (Sugawara et al, 2005;Dungan et al, 2016;Xia et al, 2021). In addition, the analysis of differential selection further confirmed that COL8A2 was subject to differential selection among different aquatic environments (Table 2 and Figure 7).…”
Section: Corneal Adaptation Of Mudskipperssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results revealed a significant correlation between COL8A2 evolution and maximum diving depth (Figure 8), which indicated selection on genes imposed by diving depth. This conclusion is consistent with the finding of a previous study on RH1 that water depth adaptation has a significant impact on the evolution of vision (Sugawara et al, 2005;Dungan et al, 2016;Xia et al, 2021). In addition, the analysis of differential selection further confirmed that COL8A2 was subject to differential selection among different aquatic environments (Table 2 and Figure 7).…”
Section: Corneal Adaptation Of Mudskipperssupporting
confidence: 91%
“…For example, the visual system of the Mariana lionfish (Pseudoliparis swirei) has been severely degraded due to its adaptation to darkness (Jiang et al, 2019). In many deep-diving groups, the rhodopsin RH1 gene, which mainly mediates scotopic vision (Lythgoe and Dartnall, 1970;Yokoyama et al, 2008), has not only evolved rapidly but also mutated in amino acid (AA) sequences with similar functional properties, resulting in adaptive evolution of protein functions (Xia et al, 2021). In addition, in the color vision system, cone cells and related genes (SWS1, LWS, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The divergent evolution of cetacean SAG has been suggested to be associated with their deep diving, and a key substitution (Q69R) has been verified for having a role in increasing the formation of rhodopsin Meta II (Chiu, 2019). In addition to their specialized rhodopsins (significantly faster retinal release rates and possibly faster dark adaptation; Xia et al, 2021;Dungan and Chang, 2022), SAG could be another gene contributing to the acute dim-light vision of deep-diving species, by regulating Meta II formation and thus possibly accelerating the rod dark adaptation (Frederiksen et al, 2016). Since the key substitution found in whales (Chiu, 2019) is not shared with penguins and seals (Supplementary Figure S2), their potential fast adaptation to deep-diving visual perception via rod arrestin might be due to different molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…For cetaceans, since ARR3 pseudogenes were found in some species (Supplementary Figure S1), and they have experienced widespread losses of opsin and some other visual genes (Meredith et al, 2013;Springer et al, 2016;McGowen et al, 2020), the significantly higher ω value for the ARR3 sequences is unlikely due to adaptation to color vision. Apart from phenotypic evolution of rhodopsin in deep-diving vertebrates (Xia et al, 2021), rhodopsin function has also been measured for the ancestor of Archosaur, which was shown to have a similar transducin activation rate as that of bovine rhodopsin (Chang et al, 2002). We therefore carried out evolutionary analyses of the archosaur SAG and ARR3 sequences to determine whether their visual arrestins experienced adaptive evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation